The Development of Simulation-Based Approach to Depression and Family Relationships in Indonesia - Li Cen; Danel Smile; Darren, Darren; Herman (Cattleya Darmaya Fortuna, 2026)
This research presents the development of Ruang Hampa, a web-based narrative simulation game designed to foster empathy and understanding of depression experiences within Indonesian family contexts. The game employs a choice-driven narrative approach in which players experience the daily challenges of a university student coping with depression while navigating complicated family relationships. The development methodology integrates the ADDIE model with User-Centered Design (UCD) principles, combining UI/UX design principles with narrative-driven gameplay mechanics utilizing mental energy and relationship management systems. The game architecture uses TypeScript for development and implements a state machine pattern for story progression through 15 interconnected narrative nodes with 45 branching choices. Key findings demonstrate that the simulation successfully translates abstract mental health concepts into tangible, interactive experiences offering three distinct endings based on player choices. The mental energy mechanic serves as a quantifiable representation of psychological well-being, while relationship values track family communication dynamics. This study contributes to the growing field of serious games for mental health by demonstrating how interactive narratives can address culturally specific challenges in Indonesian family structures. The minimalist pixel art aesthetic and retro design elements enhance the introspective atmosphere while maintaining accessibility across web platforms. Technical achievements include a 2,500-line TypeScript codebase with average load times of 2.3 seconds and successful deployment to production. Future implementations should incorporate user testing to validate the game's therapeutic effectiveness and cultural sensitivity, providing empirical evidence of its potential as an educational tool for mental health awareness in Indonesian communities.